Konsep Industrialisasi, Transformasi Struktural - Yosse Putra Oentoro; Ivonia Auxilidora Freitas Marcal; Muhammad Yasin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research explores the concepts of industrialization and structural transformation, two phenomena that are interrelated and have a crucial role in the economic development of a country. Industrialization is the process by which a country or region shifts its economy from an agricultural to an industrial basis, involving increased production of goods and services through the introduction of new technologies and increased production capacity. Structural transformation, on the other hand, refers to fundamental changes in the structure of the economy, involving a shift from the primary sector (agriculture) to the secondary (industry) and tertiary (services) sectors. This study highlights how industrialization drives structural transformation by creating new jobs, increasing productivity, and changing consumption patterns and income distribution. This research also discusses factors that influence these two processes, including government policy, foreign investment, and technological innovation. Through analysis of various cases of countries that have successfully carried out industrialization and structural transformation, this research provides insight into effective strategies that can be implemented by developing countries to achieve sustainable and inclusive economic growth.